Analysis of the Influence of Economic Growth, Average Length of Schooling, and Provincial Minimum Wage on the Open Unemployment Rate (TPT) in 6 Provinces of Java - Habibi, Muhammad Adib; Taufiq, Muhammad; Utami, Annisa Fitria (Jurnal Pemberdayaan Ekonomi dan Masyarakat, 2024)
Unemployment poses an urgent issue globally and correlates with various factors but follows a non-systematic pattern. This Study examine the impact of economic growth, minimun wages, average years of schooling on the open unemployment rate (OUR) six Province in Java Island. Using secondary panel data regression analysis from 2013 to 2022, a quantitative approach with multiple linear regression analysis was employed, processed with Eviews 13 software. The finding indicate that, simultaneously, all variables significant influence the open unemployment rate(OUR). Specifically, economic growth  shows a negative and significant effect, average length of Schooling (ALOS) has a negative and significant effect, and minimum wage has a negative and significant effect. This study provides insights into the dynamic influencing unemployment six Province in Java Island, highlighting the critical roles of minimum wage, education, and economic growth in shaping the unemployment landscape. Understanding these factors can help policymakers develop strategies to reduce unemployment and promote economic stability.